Management strategy and novel ophthalmological findings in neonatal severe hypertriglyceridemia: a case report and literature review - Nehal M. El-koofy; Yasmeen A. Abdo; Dina El-Fayoumi; Amanne F. Esmael; Mohamed. A. Elmonem; Zahraa Ezzeldin (Lipids in Health and Disease, 2021)
Abstract Background Neonatal severe hypertriglyceridemia is rarely reported in the literature and there is no consensus for hypertriglyceridemia management at this age group. Methods The index case is a 4-week-old male infant with severe hypertriglyceridemia accidentally discovered during a circumcision surgery. His clinical and genetic characteristics and his successful management strategy are described. Furthermore, a detailed ophthalmological examination of the proband was conducted at 3 and 6 months of age using Fourier-domain-optical coherence tomography. Results Triglycerides level at presentation was extremely high 33,727 mg/dL (380.8 mmol/L). Two sessions of exchange blood transfusion on two consecutive days successfully reduced triglycerides to 382 mg/dL (4.3 mmol/L) with no adverse effects. The infant was discharged 3 days later. At discharge, the mother was advised to continue breastfeeding together with a medium-chain triglycerides formula. Satisfactory growth parameters and lipid profile values were obtained for a follow-up duration of 5 months with no reported attacks of acute pancreatitis. Lipoprotein lipase deficiency was confirmed by the detection of the LPL homozygous pathogenic variant c.805G > A; p.(Glu269Lys). Early corneal and macular lesions were detected and persisted on follow-up despite relatively good lipemic control. Conclusion This case highlights the importance of the early discovery of severe hypertriglyceridemia during the neonatal period, which is needed for prompt management and prevention of severe complications. Rationalized breastfeeding can be tolerated within the diet plan of the disease with satisfactory outcomes. To our knowledge, it is the first study reporting early corneal and macular affection by severe hypertriglyceridemia in a neonate. Prolonged follow-up is needed to determine the extent of ophthalmological lesions.